Pengaruh Benefit dan Price Terhadap Perceived Value Serta Dampaknya Terhadap Keputusan Penggunaan GoTransit Pada Aplikasi Gojek - Saputro, Nugroho Danu; Baharuddin, Gunawan; Permana , Erwin (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This research aims to analyze the benefits and prices of perceived value and their impact on the decision to use GoTransit on the Gojek application. The population used in this research were commuter line train users who used GoTransit on the Gojek application, with a sample size of 105 respondents. The data collection method is through a questionnaire using gform. This research uses the Smart PLS 3.2.8 Partial Least Square (PLS) analysis technique. The results of this research show that, Benefits have a significant influence on perceived value, Price has a significant influence on perceived value, Benefits have a significant influence on purchasing decisions, Price has a significant influence on purchasing decisions, and Perceived value has an influence on purchasing decisions.